Beginning Azure static web apps : building and deploying dynamic Web applications with Blazor - Cashmore, Stacy (Apress, 2022)
Create rich and dynamic web applications on the Azure cloud platform using static web development techniques built around Blazor WebAssembly, APIs, and Markup, while leveraging the paradigm commonly known as JAMstack. This book starts off showing you how to create an environment for deploying your first application. You will create an Azure Static Web App using a Blazor WebAssembly application and adding dynamic content using an Azure function before deploying from GitHub. You will learn to debug your Static Web App locally, both inside of Visual Studio and from the command line using a simple Static Web App CLI command. The book takes a deep dive into the CLI to allow you to emulate all of the features available in the Azure environment. You will learn the authentication and authorizing options with your app and create new blog posts with the post creation function. Included in the book is setting a custom domain and discussion of the options. The book also explores the differences between the free and standard hosting tiers for Static Web Apps. After reading this book, you will be able to create Azure Static Web Apps using Blazor technology.